2005
DOI: 10.1021/ja042404n
|View full text |Cite
|
Sign up to set email alerts
|

Squaraine-Derived Rotaxanes:  Sterically Protected Fluorescent Near-IR Dyes

Abstract: A squaraine dye with bulky end groups is employed as the thread component in two Leigh-type amide rotaxanes. The rotaxanes are synthesized in a simple two-step process. X-ray crystal structures of the rotaxanes show that the pyridyl-containing macrocycle is more rigid and wraps more tightly around the cyclobutene core of the squaraine thread compared to the isophthalamide-containing macrocycle. The rotaxanes exhibit photophysical properties that are similar to the precursor squaraine. The encapsulating macrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(170 citation statements)
references
References 23 publications
4
164
0
2
Order By: Relevance
“…[63][64] They have been utilized in a variety of applications, including as chemosensors for metal ions [65][66][67][68] and thiols, 69 as indicators of membrane polarity, 70 and as guests encapsulated in aromatic macrocycles. [71][72][73] Squaraines have also been utilized extensively for biological imaging. [74][75] The absorption and fluorescence maxima of fluorophores in spin-cast PMMA films and their extinction coefficients a at their absorption maxima.…”
Section: Methodsmentioning
confidence: 99%
“…[63][64] They have been utilized in a variety of applications, including as chemosensors for metal ions [65][66][67][68] and thiols, 69 as indicators of membrane polarity, 70 and as guests encapsulated in aromatic macrocycles. [71][72][73] Squaraines have also been utilized extensively for biological imaging. [74][75] The absorption and fluorescence maxima of fluorophores in spin-cast PMMA films and their extinction coefficients a at their absorption maxima.…”
Section: Methodsmentioning
confidence: 99%
“…Arunkumar and Smith introduced a smart supramolecular approach to solve both problems at the same time: the encapsulation of the squaraine as the thread component inside an interlocked rotaxane structure. [13] Scheme 13.…”
Section: Squaraine-based Rotaxanesmentioning
confidence: 99%
“…All of these favourable features promote their exploitation in a number of technologically relevant applications including photoconductivity [3] data storage, [4] light emitting field-effect transistors, [5] solar cells [6][7][8] and nonlinear optics. [9] Recently, it has been shown that squaraines can also behave as very efficient two-photon absorbers, [10] fluorescent histological probes, [11] highly stable fluorescent near-IR dyes, [12,13] active media for fluorescence patterning [14] and possibly as second-generation photosensitizers for photodynamic therapy (PDT). [15,16] Aim of the present review is to summarize the most convenient strategies for squaraines and polysquaraines syntheses and to discuss the design strategies enabling for the preparation of squaraines having properties relevant for a given materials application.…”
Section: Introductionmentioning
confidence: 99%
“…[35] The thread component is a squaraine dye which emits potentially useful near-IR fluorescence, however, two drawbacks are the dye's suscep- tibility to nucleophilic attack [36] and aggregate formation. [37] These problems were rectified by converting the dye into a rotaxane.…”
Section: Rotaxane Dyesmentioning
confidence: 99%